Pengaruh Metode KWL (Know-Want-learn) terhadap Minat Membaca pada Pembelajaran Bahasa Indonesia Kelas IV SDN Kertajaya IV Surabaya - Isnaini Fadya Rahmadani; Afib Rulyansah; Suharmono Kasiyun; Dewi Widiana Rahayu (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
This research is motivated by students' lack of interest in reading in learning Indonesian. As a solution, this study applies the KWL (Know-Want-Learn) learning model in Indonesian language learning in class IV SDN Kertajaya IV Surabaya. The purpose of this study was to determine the extent to which the KWL (Know-Want-Learn) technique influences the reading interest of fourth grade students at SDN Kertajaya IV in Surabaya in learning Indonesian. This study is based on the KWL learning paradigm, which requires three main learning activities: students' active participation before reading, understanding the text when it is read, and the ability to draw conclusions. This study used a questionnaire, pretest, and posttest to evaluate the impact of the KWL learning approach on reading ability. The average score obtained by students in the pretest was 64, while the average score they received in the posttest was 82. Therefore, the demands of mastery learning depend on the effectiveness of the KWL learning approach.